International supply chain management. Study guide - Ширяєва, Наталя Володимирівна; Макаренко, Анастасія Борисівна; Білоцерківський, Олександр Борисович (My University, 2020)
In these guidelines, the main numerical methods that are used in the course "International Logistics" are considered. Each section is dedicated to a separate topic of the course. All sections are constructed in the same way: first, the necessary theoretical information, then a detailed course of solving problems, and at the end of each section, options for individual homework. Variants of the tasks should be selected by the student’s last name in the group’s journal. The instructions also contain control questions to test students' knowledge.
Keywords: international logistics; purchasing logistics; distribution logistics; logistics of stocks; warehouse logistics